Stumbling blocks between presenter and audience: a study on contributing factors that hinder students to ace in ESL Oral Presentation / Muhd Syahir Abdul Rani and Nurul Farhani Che Ghani - Abdul Rani, Muhd Syahir; Che Ghani, Nurul Farhani (2019)
The purpose of this study is to examine the main contributing factors that hinder students to ace in ESL oral presentations. It also investigates whether there exists any significant difference between both genders and the correlation between audience behavior and the contributing factors which encompass language, content and delivery. A total of 144 undergraduate students from 3 different faculties, namely Accountancy, Applied Science and Computer and Mathematical Science, participated in the study. The data obtained were analyzed using SPSS software Version 20. The results of the analysis indicate that the main factor contributing to low marks in oral presentations is the students’ fluency, followed by sentence structures in oral speeches, and pronunciation. Independent T-test was carried out and the results were compared based on genders. The results reveal that male students received significantly lower marks for “Relevance” and “effectiveness”, thus reveals that male students are less effective and less relevant in the assessment. This study also discovers that there exists a moderate relationship between the method of delivery during oral presentation and the audience’s behavior